If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(b+-42)=-66
We move all terms to the left:
3(b+-42)-(-66)=0
We add all the numbers together, and all the variables
3(b-42)-(-66)=0
We add all the numbers together, and all the variables
3(b-42)+66=0
We multiply parentheses
3b-126+66=0
We add all the numbers together, and all the variables
3b-60=0
We move all terms containing b to the left, all other terms to the right
3b=60
b=60/3
b=20
| w-5.58=4.65 | | 5y-2y+9=0 | | 16v+101+47=180 | | 7b+4b-1b=12b | | F(n)=1(2)n | | 2x+10=-6x-22 | | (x)+8=19 | | n-575=24 | | -2x+12=2x-8 | | 2x+10=-6x-22 | | 87=29a | | 24x+5+61x+5=180 | | 2(4x+7)=3(2+3x) | | X+9=1/7y | | -8(-8x–6)=-6x–22 | | 24+5+61x+5=180 | | 6y-2y+8=0 | | -7/8x-9/40x+1/5x=-72 | | 70=d+7 | | 5-(x+2)=2x | | 13x+11=5x+35 | | 6.8–4.2b=5.6b–3 | | -16+5x=-6 | | 6y-27+8=0 | | -x+6/2=7 | | -5x+-3*6=10 | | 16-5x=26 | | 15=a+14 | | 3a+5a+2a=180 | | y^2-3=46 | | 52-(3x+4)=4(x+6) | | 275^x−4=81^7x−2 |